2022
DOI: 10.3389/fpsyt.2022.838903
|View full text |Cite
|
Sign up to set email alerts
|

“Post-lockdown Depression”: Adaptation Difficulties, Depressive Symptoms, and the Role of Positive Solitude When Returning to Routine After the Lifting of Nation-Wide COVID-19 Social Restrictions

Abstract: ObjectivesThe aim of the current study was to identify difficulties in adapting to normal life once COVID-19 lockdown has been lifted. Israel was used as a case study, as COVID-19 social restrictions, including a nation-wide lockdown, were lifted almost completely by mid-April 2021, following a large-scale vaccination operation.MethodsA sample of 293 mid-age and older Israeli adults (M age = 61.6 ± 12.8, range 40–85 years old) reported on return-to-routine adaptation difficulties (on a novel index), depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 44 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…However, in the Spanish population [ 72 ], the negative effects of the pandemic on the increase in DS were exacerbated 1 year after the onset of the pandemic. Moreover, in the Israeli population ( n = 293, aged 40–85 years) [ 25 ], following the removal of social restrictions, people had difficulty adjusting to the return to routine (44% with moderate to high levels of difficulty), and higher levels of adjustment difficulty were associated with higher levels of DS (β = 0.15, t = 2.34, p < 0.05). Furthermore, middle-aged adults presented higher levels of depressive symptoms and adjustment difficulty (48.7% and 24.7%, respectively) compared to older adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the Spanish population [ 72 ], the negative effects of the pandemic on the increase in DS were exacerbated 1 year after the onset of the pandemic. Moreover, in the Israeli population ( n = 293, aged 40–85 years) [ 25 ], following the removal of social restrictions, people had difficulty adjusting to the return to routine (44% with moderate to high levels of difficulty), and higher levels of adjustment difficulty were associated with higher levels of DS (β = 0.15, t = 2.34, p < 0.05). Furthermore, middle-aged adults presented higher levels of depressive symptoms and adjustment difficulty (48.7% and 24.7%, respectively) compared to older adults.…”
Section: Discussionmentioning
confidence: 99%
“…In the first waves of the pandemic, during mandatory confinement, people presented a deterioration in their mental health [ 22 , 23 ]; according to the WHO, the pandemic triggered a 25% increase in the prevalence of depression worldwide [ 24 ]. Furthermore, according to Keisari et al [ 25 ], several depressive symptoms persisted despite the removal of social restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…This is important, because other studies’ findings show that maintaining a connection to different dimensions of spirituality is associated with better mental health and coping in times of adversity, both in general ( Whitehead and Bergeman, 2012 ; Thauvoye et al, 2018 ; Lifshitz et al, 2019 ) and specifically during the COVID-19 pandemic ( Ribeiro et al, 2020 ; Lucchetti et al, 2021 ; Keisari et al, 2022c ). The ability of the intervention to connect the participants to the various domains of spiritually as coping resource is crucial, since studies have shown that the COVID social distancing restrictions caused psychological distress for many, including more symptoms of depression ( Fountoulakis et al, 2022 ; Keisari et al, 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…Social restrictions introduced in response to the COVID-19 pandemic have caused many people psychological distress ( Zhu et al, 2021 ; Keisari et al, 2022a ). Social distancing mandates particularly affected older adults who live alone or rely on psycho-social support outside the home ( Morrow-Howell et al, 2020 ; Steinman et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The social restrictions imposed by the COVID-19 pandemic further limit interactions and other opportunities for cognitive exercise (eg, work and volunteering). Indeed, current restrictions have been found to increase loneliness and depression in older age [ 22 ], even after vaccinations were made available [ 23 ] and severe social restrictions were lifted [ 24 ]. These, together with limited access to health care services as a result of the pandemic [ 25 , 26 ], illustrate the necessity to create effective SGCTAs that can directly affect spoken communication in adverse conditions, even while social distancing.…”
Section: Introductionmentioning
confidence: 99%